Contemporary social work practice : a handbook for students - Teater, Barbra (Maidenhead : Open University Press, 2014)
Students often enter social work education with a very limited knowledge of the many different and varied roles that social workers undertake across the statutory and voluntary sectors. This book provides an in-depth overview of fifteen different contemporary social work practice settings, ranging from mental health to fostering and adoption, and alcohol and drug treatment services to youth offending.
Includes bibliographical references and index.
Keywords: Social case work